A molecular dynamics simulation framework for predicting noise in solid-state nanopores. Issue 13 (1st September 2020) - Patil, Onkar; Manikandan, D.; Nandigana, Vishal V. R.
ABSTRACT: In this paper, we perform all-atom molecular dynamics (AA-MD) simulations to predict noise in solid-state nanopores. The simulation system consists of ∼70, 000 to ∼350, 000 atoms. The simulations are carried out for ∼1.3 µs over ∼6500 CPU hours in 128 processors (Intel ® E5-2670 2.6 GHz Processor). We observe low and high frequency noise in solid-state nanopores. The low frequency noise is due to the surface charge density of the nanopore. The high frequency noise is due to the thermal motion of ions and dielectric material of the solid-state nanopore. We propose a generalised noise theory to match both the low and high frequency noise. The study may help ways to study noise in solid-state nanoporous membranes using MD simulations.